INVOLVEMENT OF CHILDREN IN HADANAH PROCEEDING IN MALAYSIAN SYARIAH COURT: AN APPRAISAL - Nadia Murshida Abd Azzis; Alias Azhar (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This writing examines the procedure in arriving at a decision in child custody cases. With the existence of the legal provisions; be it substantial law or procedural law; in all States, there are still unclear application of the concept of best interest of child or welfare of the child especially in their involvement in court proceedings in custodial issues. Although the term ‘welfare’ has been precisely constructed in the relevant Enactments, the harmonization between the concept of welfare and child participation in court proceedings is yet to be scrutinized by the Courts. Battle custody and guardianship cases in Syariah courts seems to focus the issue of qualified or unqualified custodian and guardian. As such, the concern of the court might divert from the child; as the subject matter; to the spouses since the issue brought up referring to the custodian. Thus, an empirical research was carried out along with library research in this qualitative writing. Data is analysed utilizing case study and content analysis method. This study indicated that Syariah Court procedures in arriving at a decision of child custody cases are sufficient. However, in order to safeguard the interest of parents and children, there are possible betterment of court due process in the context of implementation of certain procedures such as to how child interview and opinion should be conducted in practice particularly in order to fulfil the concept of best interest of child and welfare of the child.